2001
DOI: 10.1007/bf03401965
|View full text |Cite
|
Sign up to set email alerts
|

Human Endotoxemia Activates p38 MAP Kinase and p42/44 MAP Kinase, But Not c-Jun N-terminal Kinase

Abstract: Background: All three major members of the MAPK family (i.e., p38 MAPK, p42/p44 MAPK, and c-Jun N terminal kinase (JNK)) have been shown to control cellular responses to inflammation in vitro. Therefore these kinases have been designated suitable targets for anti-inflammatory therapy. However, the extent to which these kinases are actually activated during inflammation in humans in vivo has not been investigated. We employed experimental human endotoxemia, a model of systemic inflammation, to address this ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…The p38 and p42 MAPK activation is transient (41,42). The activation dynamics of p38 and p42 could be such that the peak of their activation has passed already at the three-hour time point, which is in accordance with studies in human endotoxemia studies: after an early peak of activation for both p38 and p42, a reduced phosphorylation state occurred (43). To investigate the full activity dynamics of p38 and p42, in future studies, kinome analysis on earlier time points should be performed.…”
Section: R E S E a R C H A R T I C L E M O L M Esupporting
confidence: 76%
“…The p38 and p42 MAPK activation is transient (41,42). The activation dynamics of p38 and p42 could be such that the peak of their activation has passed already at the three-hour time point, which is in accordance with studies in human endotoxemia studies: after an early peak of activation for both p38 and p42, a reduced phosphorylation state occurred (43). To investigate the full activity dynamics of p38 and p42, in future studies, kinome analysis on earlier time points should be performed.…”
Section: R E S E a R C H A R T I C L E M O L M Esupporting
confidence: 76%
“…Inflammatory mediators such as tumour necrosis factor (TNF) and interleukin-1 (IL-1) activate p38 MAPK, JNK and p42/44 MAPK [32,33]. Ikeda et al [34] also found evidence that cellular Ca 2+ acts as an upstream modulator of p38 MAPK.…”
Section: Discussionmentioning
confidence: 91%
“…Signaling pathways necessary for systemic inflammation in humans are p38 MAPK and extracellular signal-regulated kinase (ERK) but not c-jun N-terminal kinase (JNK) [8]. In in vitro studies, blockade of p38 MAPK with SB203580 inhibited chemotactic movement of human neutrophils in a concentrationdependent manner [9] and prevented stimulus-induced formation of a leading edge in neutrophils by causing filamentous (F) actin to localize peripherally instead of in the lamellipod [10].…”
Section: Introductionmentioning
confidence: 99%